The Cortico-Basal Ganglia-Cerebellar Network: Past, Present and Future Perspectives - Milardi, Demetrio; Quartarone, Angelo; Bramanti, Alessia; Anastasi, Giuseppe; Bertino, Salvatore; Basile, Gianpaolo Antonio; Buonasera, Piero; Pilone, Giorgia; Celeste, Giuseppe; Rizzo, Giuseppina; Bruschetta, Daniele; Cacciola, Alberto (Frontiers in Systems Neuroscience, 2019)
Much of our present understanding of the function and operation of the basal ganglia rests on models of anatomical connectivity derived from tract tracing approaches in rodents and primates. However, the last years have been characterized by promising step forwards in the in vivo investigation and comprehension of brain connectivity in humans. The aim of this review is to revise the current knowledge on basal ganglia circuits, highlighting similarities and differences across species, in order to widen the current perspective on the intricate model of the basal ganglia system. This will allow us to explore the implications of additional direct pathways running from cortex to basal ganglia and between basal ganglia and cerebellum recently described in animals and humans.